Discovery of synthetic lethal interactions from large-scale pan-cancer perturbation screens - Sumana Srivatsa; Hesam Montazeri; Gaia Bianco; Mairene Coto-Llerena; Mattia Marinucci; Charlotte K. Y. Ng; Salvatore Piscuoglio; Niko Beerenwinkel (Nature Communications, 2022)
Synthetic lethality can be used to identify potential drug targets in cancer based on simultaneous inactivation of two genes through genetic aberrations and gene silencing. Here, the authors develop a statistical framework to identify synthetic lethal pairs from large scale perturbation screens across multiple cancer types.